Ovipositional Preferences of Two Squash Bug Species, Anasa tristis and Anasa armigera (Heteroptera: Coreidae), for Different Cultivars and Species of Cucurbitaceae. Issue 2 (17th March 2018) - Cornelius, Mary L
Abstract: The ovipositional preferences of two squash bug species, Anasa tristis (DeGeer) (Heteroptera: Coreidae) and Anasa armigera Say (Heteroptera: Coreidae), were evaluated in paired choice tests of different species and cultivars of plants in the family Cucurbitaceae. Females of A. tristis preferred to oviposit on the cultivar from which they were reared over three other cultivars of the same species. However, females did not show any ovipositional preference for different cultivars when they had no previous exposure to either cultivar. Females of A. tristis were equally likely to oviposit on Cucurbita pepo, Cucurbita maxima, and Cucurbita moschata but were significantly more likely to oviposit on C. pepo than on cucumber and watermelon. Females of A. armigera were equally likely to oviposit on C. pepo or cucumber, regardless of the species they were reared on. When A. armigera was reared on C. pepo, females were more likely to oviposit on C. maxima than on cucumber and less likely to oviposit on C. moschata than on cucumber.